A MOF-derived CuCo(O)@ carbon–nitrogen framework as an efficient synergistic catalyst for the hydrolysis of ammonia borane. Issue 10 (21st April 2020) - Yuan, Yao; Chen, Xiaoyu; Zhang, Xing; Wang, Zumin; Yu, Ranbo
Abstract : A CuCo(O)-embedded nitrogen-enriched porous carbon framework catalyst derived from doped metal–organic frameworks for efficient hydrolysis of ammonia borane. Abstract : Ammonia borane (AB), with a potential storage capacity of 19.6 wt% H2, is an excellent material for chemical storage of hydrogen. However, the use of noble metal catalysts severely hinders the practical application of AB decomposition for hydrogen generation. In this work, well dispersed CuCo and CoO nanoparticles (CuCo(O)) supported on carbon–nitrogen frameworks (CN) have been synthesized through a facile thermal reduction of the Cu-doped ZIF67 precursor. Upon reduction, Co and Cu in the ZIF framework are partially reduced into CuCo particles of about 30 nm, and these active species are anchored on porous carbon–nitrogen matrix inherited ZIF frameworks (denoted as CuCo(O)@CN). The as-prepared material demonstrates a ZIF-67-like polyhedral morphology, good nanoparticle spatial distribution and better active site availability. When used as an AB hydrolysis catalyst, CuCo(O)@CN exhibits excellent catalytic activity, with the highest catalytic efficiency up to 4524 mL min −1 g −1 and a total turnover frequency (TOF) of 12.4 mol H2 per min per molcat, which are among the best performances of noble metal-free catalysts. In addition, the corresponding activation energy is estimated to be as low as 33.8 kJ mol −1 . Detailed analysis suggests that excllent catalytic performance could be attributed to the synergy between Co and Cu as well as the nitrogen-rich carbon support.